Insulin Resistance and the Effect of Insulin on Blood Pressure in Essential Hypertension - Heise, Tim; Magnusson, Kai; Heinemann, Lutz; Sawicki, Peter T. (Hypertension (Dallas, Tex. 1979), 1998)
The aim of this study was to investigate the effect of 2 weeks of insulin administration on blood pressure and to simultaneously measure insulin sensitivity and insulin-induced vasodilatation in obese hypertensive patients. In a prospective, randomized, double-blind, crossover study (study 1), 23 obese, untreated, nondiabetic, hypertensive patients received either neutral protamine Hagedorn (NPH) insulin (0.3 U/kg body wt per day) or placebo subcutaneously for 2 weeks (washout period, 2 weeks). Office and 24-hour blood pressure values were measured at the beginning and end of each treatment period. In an open-label study (study 2), 8 obese hypertensive patients and 10 healthy control subjects underwent a 3-step hyperinsulinemic, euglycemic glucose clamp (step 1, 0.5; step 2, 2.5; step 3, 5.0 mU [middle dot] kg [middle dot] min [120 minutes each]). Leg blood flow (LBF) was measured by venous occlusion plethysmography. Insulin administration decreased mean +/- SD office blood pressure from 131 +/- 13 to 128 +/- 12 mm Hg (placebo, 132 +/- 13 and 132 +/- 13 mm Hg; P<0.05 between final examinations) and mean +/- SD 24-hour blood pressure by -3.3 +/- 6.9 mm Hg (placebo, +0.7 +/- 4.6 mm Hg; P<0.05). Insulin infusion increased LBF significantly in the healthy controls but not in obese insulin-resistant hypertensive subjects. Obese hypertensive patients are resistant to the effects of insulin with regard to both glucose uptake and vasodilatation. Administration of insulin exerts a small blood pressure-lowering effect in these patients. These data strongly argue against the postulated pressor action of insulin in essential hypertension. (Hypertension. 1998;32:243-248.)